2007
DOI: 10.1253/circj.71.52
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Aortic Plaque Enhances Hypercoagulability in Patients With Nonrheumatic Atrial Fibrillation

Abstract: trial fibrillation (AF) is associated with higher thromboembolic risk, possibly because of the hypercoagulable state. 1,2 Elevated levels of hemostatic markers have been shown in patients with nonrheumatic AF. [2][3][4][5][6] During AF, stagnation of blood flow in the left atrial appendage (LAA) could contribute to the hypercoagulable state and clot formation in the fibrillating atria. Hemostatic markers could be therefore used for stratification of patients at high risk vs low risk for thromboembolism as demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…42,43,45 In the present study, a significant positive correlation was found between plasma D-dimer and BNP levels. Therefore, we suggest that a high plasma BNP level might indicate a hypercoagulate state in very elderly patients who have non-valvular AF without overt heart failure.…”
Section: Discussionsupporting
confidence: 68%
“…42,43,45 In the present study, a significant positive correlation was found between plasma D-dimer and BNP levels. Therefore, we suggest that a high plasma BNP level might indicate a hypercoagulate state in very elderly patients who have non-valvular AF without overt heart failure.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, we have shown in the present study that the severity of aortic atherosclerosis was associated with an increase in the risk level. Aortic atherosclerosis might be associated with a hypercoagulable state in patients with AF, resulting in a high prevalence of cerebral infarction [15].…”
Section: Atherosclerosis Of Descending Aortamentioning
confidence: 99%
“…The existence of complex aortic plaques is considered to be a marker of atherosclerosis, and is known to enhance hypercoagulability in patients with NVAF 15. Therefore, the development of an accurate ischemic stroke risk stratification scheme that would include certain types of laboratory data such as TEE risk markers that directly reflect a prothrombotic condition of the LA is warranted 16,17…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further studies are warranted to evaluate the correlation between LVEF and LAD, and the presence of TEE risk. The addition of hemostatic markers, such as D-dimer levels, to the criteria for stroke risk stratification should also be considered 15,18,19…”
Section: Discussionmentioning
confidence: 99%